Electrical acupoint stimulation increases athletes' rapid strength - Yang, H. Y.; Liu, T. Y.; Kuai, L.; Gao, M. (Zhongguo Zhen Jiu, 2006)
OBJECTIVE: To search for a stimulation method for increasing athletes' performance. METHODS: One hundred and fifty athletes were randomly divided into a trial group and a control group, 75 athletes in each group. Acupoints were stimulated with audio frequency pulse modulated wave and multi-blind method were used to investigate effects of the electric stimulation of acupoints on 30-meter running, standing long jumping and Cybex isokinetic testing index. RESULTS: The acupoint electric stimulation method could significantly increase athlete's performance (P < 0.05), and the biomechanical indexes, maximal peak moment of force (P < 0.05), force moment accelerating energy (P < 0.05) and average power (P < 0.05). CONCLUSION: Electrical acupoint stimulation can enhance athlete's rapid strength